2008
DOI: 10.1039/b807090n
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous divalent metal–nitrate interactions: hydration versus ion pairing

Abstract: Nitrate aqueous solutions, Mg(NO(3))(2), Ca(NO(3))(2), Sr(NO(3))(2), and Pb(NO(3))(2), are investigated using Raman spectroscopy and free energy profiles from molecular dynamics (MD) simulations. Analysis of the in-plane deformation, symmetric stretch, and asymmetric stretch vibrational modes of the nitrate ions reveal perturbation caused by the metal cations and hydrating water molecules. Results show that Pb(2+) has a strong tendency to form contact ion pairs with nitrate relative to Sr(2+), Ca(2+), and Mg(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
107
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 47 publications
12
107
1
2
Order By: Relevance
“…Raman spectra of the ATM-109 fuel solutions with variable HNO 3 associated for the υ 1 symmetric stretch (∼ 1050 cm −1 ), υ 3 asymmetric stretch (∼ 1350 cm −1 ), and υ 4 in-plane deformation (∼ 700 cm −1 ) modes were observed; the υ 2 band for nitrate is Raman forbidden and was not observed [40][41][42]. The 718 cm −1 band is assigned to the υ 4 in-plane deformation mode of the nitrate moiety, and has E symmetry in D 3h ; this band splits into A 1 and B 2 pairs upon descent in symmetry to C 2v when undergoing interaction with cations (such as H + , or UO 2 2+ ); the two Raman bands observed at 644 and 697 cm −1 were assigned to these modes in the 5.1 M HNO 3 spectrum.…”
Section: Resultsmentioning
confidence: 96%
“…Raman spectra of the ATM-109 fuel solutions with variable HNO 3 associated for the υ 1 symmetric stretch (∼ 1050 cm −1 ), υ 3 asymmetric stretch (∼ 1350 cm −1 ), and υ 4 in-plane deformation (∼ 700 cm −1 ) modes were observed; the υ 2 band for nitrate is Raman forbidden and was not observed [40][41][42]. The 718 cm −1 band is assigned to the υ 4 in-plane deformation mode of the nitrate moiety, and has E symmetry in D 3h ; this band splits into A 1 and B 2 pairs upon descent in symmetry to C 2v when undergoing interaction with cations (such as H + , or UO 2 2+ ); the two Raman bands observed at 644 and 697 cm −1 were assigned to these modes in the 5.1 M HNO 3 spectrum.…”
Section: Resultsmentioning
confidence: 96%
“…The very recent work reported by Xu et al has also confirmed the CIPs exist barely in the Mg(NO 3 ) 2 solution by using the molecular dynamics (MD) simulation. 49 At last, the ion-associated process is not as simple as that suggested by Eigen and Tamm, which contains the dehydration between only two aqueous ions. From Figure 8, it can be known that the TI and MI clusters possess important status in the associated process.…”
mentioning
confidence: 98%
“…It is believed that Na + ions tends to form CIPs while Mg 2+ usually maintains its hydration structure. Xu et al 16 suggested that the formation of CIPs in Mg(NO 3 ) 2 solutions is thermodynamically unfavorable. According to the free‐energy profile of MgNO 3 + , the free‐energy minimum for CIP is significantly higher (>9 kcal mol −1 ) than those for solvent‐shared and solvent‐separated ion pairing.…”
Section: Resultsmentioning
confidence: 99%
“…Fleissner et al 15 estimated that the molar Raman intensities of the bound and free forms of nitrate are equal. Based on this assumption, Xu et al 16 revealed a linear correlation between the sum intensity of the nitrate in‐plane deformation (IPD) bands and the concentration, indicating that the IPD intensity is not significantly sensitive to the relative amount of free or ion paired species. According to a hypothesis that RSCS is unchanged from dilute solutions to supersaturated aerosols, Zhao et al 17 investigated the state of water in supersaturated Mg(NO 3 ) 2 and NaNO 3 aerosols through the application of the Raman difference spectroscopy.…”
Section: Introductionmentioning
confidence: 99%